Effectiveness of Commercial Biofertilizer on Fertilization Efficiency in Ultisols for the Growth and Yield of Caisim - Ea Kosman Anwar; Subowo Gitosuwondo (JOURNAL OF TROPICAL SOILS, 2011)
The effectiveness of Commercial Biofertilizer 1 (CBF1) on the growth and yield of caisim (Brassica sp.) was examined in the greenhouse of Indonesian Soil Research Institute in Bogor. The completely randomized design (CRD) was performed to examine the effects of Commercial Biofertilizer 1 (CBF1) on Fertilization Efficiency in Ultisols. The treatments were consists of 10 combinations between NPK-recommendation (NPK-rec) and CBF1, with six replications. The experiment was conducted from August to October 2009. The result showed that CBF I increased the yields of caisim when combining by fertilizer NPK-rec, while giving CBF1 alone did not significantly increases yields compare to control (without fertilizer). Giving ¾ dosage NPK-rec. + CBF1 had RAE value 163%, indicating the effectiveness of  CBF1 was optimum, that it reduce the need of NPK fertilizer by 25% by providing the increasing of yield  63% compared to NPK rec. The higher the level of NPK-rec. the lower the efficiency of fertilization. CBF1 had given effectives on yields when it was combined by inorganic fertilizer. However, when it was not combined with inorganic fertilizers, it would harm plants and decreased the soil nutrients.  The influence of biofertilizer in plants were predictable unpredictable, while the influent of inorganic fertilizers were predictable.